The promoter of the Chinese hamster ovary dihydrofolate reductase gene regulates the activity of the local origin and helps define its boundaries - Saha, Swati (Cold Spring Harbor Laboratory Press, 2004)
The dihydrofolate reductase (DHFR) and 2BE2121 genes in the Chinese hamster are convergently transcribed in late G(1) and early S phase, and bracket an early-firing origin of replication that consists of a 55-kb zone of potential initiation sites. To test whether transcription through the DHFR gene is required to activate this origin in early S phase, we examined the two-dimension (2D) gel patterns of replication intermediates from several variants in which parts or all of the DHFR promoter had been deleted. In those variants in which transcription was undetectable, initiation in the intergenic spacer was markedly suppressed (but not eliminated) in early S phase. Furthermore, replication of the locus required virtually the entire S period, as opposed to the usual 3–4 h. However, restoration of transcription with either the wild-type Chinese hamster promoter or a Drosophila-based construct restored origin activity to the wild-type pattern. Surprisingly, 2D gel analysis of promoterless variants revealed that initiation occurs at a low level in early S phase not only in the intergenic region, but also in the body of the DHFR gene. The latter phenomenon has never been observed in the wild-type locus. These studies suggest that transcription through the gene normally increases the efficiency of origin firing in early S phase, but also suppresses initiation in the body of the gene, thus helping to define the boundaries of the downstream origin.